Reliability and validity of the Perceived Stress Scale-10 in Hispanic Americans with English or Spanish language preference. (April 2019) - Baik, Sharon H; Fox, Rina S; Mills, Sarah D; Roesch, Scott C; Sadler, Georgia Robins; Klonoff, Elizabeth A; Malcarne, Vanessa L
This study examined the psychometric properties of the Perceived Stress Scale-10 among 436 community-dwelling Hispanic Americans with English or Spanish language preference. Multigroup confirmatory factor analysis examined the factorial invariance of the Perceived Stress Scale-10 across language groups. Results supported a two-factor model (negative, positive) with equivalent response patterns and item intercepts but different factor covariances across languages. Internal consistency reliability of the Perceived Stress Scale-10 total and subscale scores was good in both language groups. Convergent validity was supported by expected relationships of Perceived Stress Scale-10 scores to measures of anxiety and depression. These results support the use of the Perceived Stress Scale-10 among Hispanic Americans.